Gross Value Added and Total Factor Productivity In Czech Sectors - Tomáš Volek; Martina Novotná (Contemporary Economics)
The main purpose of this paper is to consider the development of total factor productivity in the development of gross value added in individual sectors of the economy of the Czech Republic in the period from 1996 - 2011. The National Account was the source of the data. The paper addresses the importance of extensive and intensive sources of economic growth in individual sectors. It was found that the development of total factor productivity does not match the growth of gross value added. The growth of gross value added was significantly influenced by extensive and intensive sources of growth in all of the economy and its sectors. The hypothesis stating that if the total factor productivity rises faster than the gross value added, then the extensive factor is negative was accepted for all sectors of the economy. The influence of intensive factors was primarily found in the manufacturing and commercial service sectors. The results of this study indicate differences in the sources of growth in individual sectors.